Exchange rate regimes and location - Luca Antonio Ricci (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper investigates the effects of fixed versus flexible exchange rate regimes on location choices of firms and on the degree of specialization of countries. In a two-country two-differentiated-good monetary model, demand, supply, and monetary shocks arise after wages are set and prices are optimally chosen. The exchange rate performs then an adjustment role for firms located in the country relatively specialized in the good they produce, but it constitutes a factor of disturbance for the others. As firms choose ex-ante the location that offers the higher expected profits for their industry, we find that countries are more specialized under flexible exchange rates than under fixed rates. One important implication is that the adoption of a fixed exchange rate regime increases the desirability of such a currency area, as it induces sectoral dispersion of production and consequently reduces the degree of asymmetry of shocks.
Keywords: 330; Internationale Arbeitsteilung; Produktionsstandort; Wechselkurs; Optimaler Währungsraum; Theorie